Komikalisasi Politik Pada Program Televisi Kabar Bang One: Episode Dipercaya (Analisis Visual Semiotika Roland Barthes ) - Sjafi’i, Ahmad; Mujiyono, Mujiyono (Capture : Jurnal Seni Media Rekam, 2014)
The focus of this study is the problem of how to structure political content displayedcomically in visual of the characters of the news program Bang One: Episode Dipercayain TV One, by Roland Barthes semiotic viewpoint. This study used a qualitative descriptivemethod. This research analyzes the characters and visual elements on the news BangOne: Episode Dipercaya. In order to assess the political concepts contained in newsprograms Bang One: Episode Dipercaya, used descriptive structure approach. The maindata sources in this study is a video news show Bang One: Episode Dipercaya equippedwith supporting data in the form of written sources and pictures. The results showedthat the visual concept characterizations of the characters in news programs Bang One:Episode Dipercaya based on conflict is relied on the work on the arrest of the criminalswho cause a crisis of confidence personal to the communal. This concept is shownthrough the medium of animation that describes the role of the characters and theirinteraction with the visual setting concept of location; supporting visual elements suchas text, bumper opening, and said balloon; and scenes each scene in news programs BangOne: Episode Dipercaya.Keywords: Bang One News, comicalization, visual, dan semiotics.